Improving the Ability to Write Short Stories through the Problem Based Learning Method with Educational Film Media for Students - Sri Rahayu Rachman; Esti Swatika Sari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to describe the improvement of the learning process in writing short stories through the problem based learning method with the educational film media of grade XI students of SMA Negeri 14 Malinau and to describe the improvement of the results of short story writing skills through the problem based learning method with the educational film media of grade XI students of SMA Negeri 14 Malinau. This research is a Class Action Research (PTK). The subject of the study was grade XI students of SMA Negeri 14 Malinau consisting of 8 students. This research was carried out in the odd semester of the 2023/2024 academic year, from January to June This action research was carried out in two cycles where in each cycle there were four components, namely planning, implementation of actions, observation, and reflection. Data collection techniques are in the form of observations, interviews, questionnaires, tests, and documentation. Data analysis techniques use qualitative and quantitative descriptive analysis techniques. Qualitative analysis is used for qualitative data in the form of interviews, field notes, and documentation of student assignments. Quantitative analysis is used for quantitative data obtained from the results of students' short story writing tests before and after being given actions as evidenced by average scores. The results of this study show that the application of educational film media can improve the ability to write short stories in learning to write short stories for grade XI students of SMA Negeri 14 Malinau. This is based on the results of the short story writing practice test of students from pre-action to cycle II has increased by 30.4. Thus, the ability to write short stories for grade XI students of SMA Negeri 14 Malinau has improved both the process and the results after being subjected to action using educational film media.